POTENSI BENCANA PELULUKAN DI DAERAH LABUHAN KABUPATEN PANDEGLANG PROVINSI BANTEN - U. M. Lumbanbatu; S. Hidayat; S. Poedjopradjitno (Pusat Survei Geologi, 2012)
Was done Labuhan, Banten Province, and sourounding area located on alluvial plain are composed of loose, water saturated clastic sediments such as gravel, sand, silt and clay, suseceptible to liquefaction. Investigation of potensial liquefaction hazards to identify degree of liquefaction susceptibility and its ditribution in investigated area. An earthquake source zone trigger liquefaction origionated by subduction activity as well as by activation of faulst on Sunda Strait. To obtain subsurface geological data hand drilling were conducted getting 59 bore holes; known a liqueable material such as sand deposited on beach sand, beach ridges, and palaeo channel deposits. On the basis of grain size distribution and its physical characteristics, stratigraphical position, ground water level, liquefaction susceptibility in this area can be divided into high liquefaction susceptibilityintermediate liquefaction susceptibility, low liquefaction susceptibility, and very low liquefaction susceptibilityKey words : liquefaction, earthquake, water saturated sand, labuhan